1946. Heterogeneous Hospitalization Outcomes of People Who Use Drugs: The Type of Drug(s) Used Matters. (26th November 2018) - Merchant, Elisabeth; Burke, Deirdre; Diaz, Chanelle; Barocas, Joshua; Tookes, Hansel; Wurcel, Alysse
Abstract: Background: US hospitals are experiencing an increase in admissions for persons who use drugs (PWUD). We examined predictors of two outcomes—leaving AMA and 30-day readmission—among PWUD. Methods: We limited the 2013 National Readmissions Database to admissions of PWUD (age 18 to 65; ICD-9 codes for illicit drugs). Diagnoses and severity (Elixhauser comorbidity index (ECI)) were defined by ICD-9 codes. Uni- and multivariable logistic regression were performed. Results: Predictors of AMA included younger age, male gender, bacterial infection, overdose, and using more than one drug. Use of opioids with stimulants was associated with the highest rate of AMA discharge (AOR 1.81, 95% CI 1.76–1.86). Leaving AMA was not found to be associated with 30-day readmission (OR 0.99, 95% CI 0.96–1.03). Conclusion: PWUD represent a heterogenous patient population with hospital outcomes influenced by different patterns of drug use. Further exploration into these differences could have implications for predicting and intervening to prevent AMA discharges as well as 30-day readmissions, which are associated with worse outcomes and significant healthcare costs. Disclosures: All authors: No reported disclosures.